Dedifferentiated adamantinoma of long bones: a case report and literature review - Xiu, Xiaofei; Li, Jiajia; Duan, Lisha; Wang, Xiaomei; Guo, Zinan; Xiao, Xuelan; Han, Qianhui; Gao, Feng (Frontiers in Oncology, 2025)
We present a rare case of dedifferentiated adamantinoma. The 48-year-old male patient was initially diagnosed with classic adamantinoma in the right fibula and underwent curettage. Two years postoperatively, the patient presented with progressive swelling and pain in the same region. Imaging disclosed an expansile lesion with mixed lytic and sclerotic changes involving the medulla and adjacent soft tissue. A biopsy was performed, and a diagnosis of classic adamantinoma was made. Considering the significant clinical symptoms and imaging features, a below-knee amputation was performed. Histologically, the tumor exhibited two distinct patterns: classic adamantinoma juxtaposed to a dedifferentiated component, characterized by chondrosarcomatous areas with moderate cellularity and abundant hyaline cartilage matrix. Myxoid areas containing malignant cartilage cells of myxoid chondrosarcoma were also observed. Immunohistochemically, the dedifferentiated areas showed complete loss of epithelial markers. At a two-year follow-up, the patient remains free of recurrence or metastasis. Dedifferentiated adamantinoma is an exceedingly rare primary bone tumor malignancy lacking specific clinical manifestations. In our case, the initial biopsy specimen revealed only epithelial cells, leading to an underdiagnosis of classic adamantinoma until further sampling revealed the dedifferentiated component. It underscores the importance of thorough sampling, close radiologic-pathologic correlation, and a multidisciplinary framework for accurate diagnosis and optimal management of complex bone tumors. Early recognition of the dedifferentiated features can guide appropriate surgical management and improve patient outcomes.